Рентгеноспектральный микроанализ минеральной структуры и химического состава марганцевого агломерата с применением в аглошихте концентрата высокоинтенсивной магнитной сепарации шламов обогащения марганцевой руды (Modern Problems of Metallurgy, 2020)
The compositions of oxide and carbonate manganese concentrates produced at the PJSC OGOK, including high-gradient magnetic separation of wet sludge, which recommended for producing of manganese sinter grade AM-2, has been analyzed. The technique was developed and research was performed for microstructure and chemical composition of mineral phases of manganese sinter which obtained in BOAF with using of electron microscopy and EPMA. Summarized and analyzed the mineral phases in the agglomerate structure according to microprobe of six material points (phases), marked on two presented electronic photographs of the microstructure with serial numbers of the spectra. The obtained results of research of microstructure and mineral phase formations during sintering of sinter charge from a mixture of various concentrates and high-intensity magnetic separation concentrate is a theoretical and experimental prerequisite for improving the complex of manganese concentrates, introduction in the compositions of sinter charges during sintering of base agglomerate AM-2 for the ferrosilicon manganese brand SiMn17 smelting.